LA INVESTIGACIÓN EDUCATIVA EN AMÉRICA LATINA Y EL CARIBE - Fiallo Rodríguez, Jorge P. (2011)
This article is an analysis of what has happened with regard to educational research in Latin America and the Caribbean, from the 1990s to date. Take into account what has happened in the educational field in that period, as well as the role played by the e. Superior in carrying out this type of research. Finally refers to institutions that primarily develop educational research and the research lines that are dedicated financial resources. This paper is an analysis of the basic regularities that took place since the early 1990s of the last century in terms of educational research in Latin America.